Sphenoid sinus hyperpneumatization: anatomical variants, molecular blueprints, and AI-augmented roadmaps for skull base surgery - Baloiu, Andra Ioana; Filipoiu, Florin; Toader, Corneliu; Covache-Busuioc, Razvan-Adrian; Munteanu, Octavian; Serban, Matei (Frontiers in Endocrinology, 2025)
The sphenoid sinus is a complex part of the skull base that has a high degree of anatomical variation, the most interesting of which occurs with hyperpneumatization, in which pneumatized air cells extend beyond their normal limits into the clivus, pterygoid processes, and sphenoidal wings. These hard to note hyperpneumatized imaging variants are disregarded in routine imaging but have potential to grossly alter important neurovascular landmarks, which is a challenge for the precision and safety of transsphenoidal surgical approaches. In this review, we provide an exten- sive, state-of-the-art investigation of sphenoid sinus hyperpneumatization, synthesizing novel pri- mary research discoveries with primordial radiological, anatomical, and clinical intrepidity. Our exploration to unravel the embryological basis for sinus development elicits an intricate balancing act between osteoclastic activity and the myriads of molecular actors such as RANKL/OPG, SHH, and BMP signaling pathways that delineate pneumatization in the skull base system. We demon- strate via in-depth radiological analysis how high-resolution CT (HRCT), dual-energy CT (DECT), and 7T MRI furnish unparalleled visualization of these variants, allowing identification of involved thinned bony walls, dehiscent canals, and high-risk zones for neurovascular insults. Clinically hy- perpneumatization is not just an anatomical curiosity, it may foreshadow operative complications and neurological symptoms. We discuss how it complicates endoscopic transsphenoidal ap- proaches and may increase the risk of internal carotid artery (ICA) injury, optic nerve impingement, and cerebrospinal fluid (CSF) leak. Surgical advances such as AR/VR-assisted neuronavigation and hydroxyapatite-based skull base reinforcement techniques are explored for their potential to de-risk these procedures and improve outcomes. Proactively, we propose that the future of sphenoid sinus hyperpneumatization research be one that adopts AI-driven morphometric analyses, clinically standardized classification systems, and longitudinal clinical studies to dissect its pathophysiolog- ical mysteries. This paper aims to develop an understanding of this omitted but clinically important anatomical variant by integrating basic anatomical principles with technology in order to provide clinicians, researchers, and surgical teams with a more nuanced, applicable exploration of the topic.